STUDIES IN MALESIAN PANDANACEAE VII. A REVIEW OF JAVANESE PANDANACEAE, WITH NOTES ON PLANTS CULTIVATED IN THE HORTUS BOGORIENSIS - Benjamin C. Stone (REINWARDTIA, 1972)
In the light of recent monographic studies it has been found necessary to augment and revise to some extent the treatment of Javanese Pandanaceae in Backer & Bakhuizen van den Brink's "Flora of Java". Several name changes are suggested and some species omitted by these authors are enumerated. Notes on various species of different origin now cultivated in the Hortus Bogoriensis are also included. Pandanus sect. Multispina Fagerlind is reduced to a subsection of Pandanus sect. Rykia.